TUJUAN HIDUP SEBAGAI TUJUAN PENDIDIKAN - Rachmad, Ferizal; Hitami, Munzir; Yusuf, Kadar M (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to discuss and describe the purpose of life as an educational goal. This research is the result of a literature review (library) which contains reviews, summaries, and written thoughts on several sources of literature, on the topics discussed. Data collection techniques are carried out by collecting books, literature articles, journals and others that are relevant to the author's title and verses of the Koran. The results of this study are that the ultimate goal of human life is also the goal of education itself. The purpose of Islamic education consists of four stages, namely: (a) the highest goal which is formulated in one term which is called: